2004
DOI: 10.1645/ge-102r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of the Haplosporidia Based on Two Independent Gene Sequences

Abstract: The phylogenetic position of the Haplosporidia has confounded taxonomists for more than a century because of the unique morphology of these parasites. We collected DNA sequence data for small subunit (SSU) ribosomal RNA and actin genes from haplosporidians and other protists for conducting molecular phylogenetic analyses to help elucidate relationships of taxa within the group, as well as placement of this group among Eukaryota. Analyses were conducted using DNA sequence data from more than 100 eukaryotic taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 23 publications
6
101
0
Order By: Relevance
“…Relationships between the four haplosporidian genera and their ascetosporean relatives were concordant with previous studies (Reece et al, 2004;Bass et al, 2009), in that Minchinia and Bonamia are resolved as monophyletic sister clades with moderate support. Together with novel lineages A and B, these are weakly sister to a large assemblage, including all Haplosporidium spp.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Relationships between the four haplosporidian genera and their ascetosporean relatives were concordant with previous studies (Reece et al, 2004;Bass et al, 2009), in that Minchinia and Bonamia are resolved as monophyletic sister clades with moderate support. Together with novel lineages A and B, these are weakly sister to a large assemblage, including all Haplosporidium spp.…”
Section: Resultssupporting
confidence: 88%
“…The reticulate amoebae, Filoreta and Gromia, are the closest known free-living relatives; phytomyxids, vampyrellids and other Cercozoa are more distantly related (Cavalier-Smith and Chao, 2003;Bass et al, 2009). There are currently four recognised haplosporidian genera: (1) Bonamia: four described species, all economically important oyster parasites in temperate waters; (2) Minchinia: a sparsely recorded genus of five species with sequence data from molluscs from the US Atlantic coast, Western Australia and Europe; (3) Urosporidium: one described species with sequence data (U. crescens; (Flores et al, 1996) and another sequenced specimen (Reece et al, 2004), both occurring as hyperparasites of trematode worms; and (4) Haplosporidium: the most intensively studied and diverse genus (approximately 40 species to date) and perhaps paraphyletic (Burreson and Ford, 2004). Most known members of the genus infect molluscs, but some infect crustaceans (Burreson and Ford, 2004;Stentiford et al, 2004) and annelids (Siddall and Aguado, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. ostreae actin genes clustered together with 100 % bootstrap support (Fig. 4A), and this grouping remained when the multiple haplosporidian paralogous sequences described by Reece and co-workers (Reece et al 2004) were included in an overall analysis (data not shown). B. ostreae appeared to be a sister clade to that formed by Minchinia tapetis and M. teredinis and Haplosporidium costale.…”
Section: Phylogeny Based On Actin Genesmentioning
confidence: 72%
“…In other protozoans, like Plasmodium falciparum, Entamoeba histolytica, several species of foraminifera and the haplosporidians Haplosporidium louisiana, Minchinia chitonis, Minchinia teredinis and Minchinia tapetis, 2-4 actin genes have been described (Huber et al 1987 ;Wesseling et al 1988 ;Pawlowski et al 1999 ;Reece et al 2004). The gene family differs in size among these organisms, and the number and location of introns within actin genes are variable (Hightower and Meagher, 1986 ;Reece et al 2004 ;Flakowski et al 2006). This study reports, through the use of nucleotide and amino acid sequence analyses, the identification of at least 2 actin genes within Bonamia ostreae.…”
mentioning
confidence: 99%